The role of probiotics in supporting celiac disease management - a review of current research and therapeutic perspectives - Cieplak, Aleksandra; Czyżewicz, Zuzanna; Kołodziej, Aleksandra; Hornig, Nadia; Zamirska, Wiktoria (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Celiac disease is a chronic autoimmune disorder that damages the small intestinal mucosa in response to the ingestion of gluten. Although a gluten-free diet is the only effective treatment, many patients experience incomplete resolution of symptoms, highlighting the need to explore new therapeutic strategies. This review aims to evaluate the available clinical evidence on the effect of probiotics on celiac disease symptoms and to analyze their potential therapeutic benefits. Materials and methods: The review was based on studies published between 2013 and 2024 that met specific inclusion criteria, such as randomization and placebo control. Trials in patients with celiac disease using different forms of probiotics, including monotherapy and mixed strains, were included. A literature search was conducted in the PubMed, EMBASE, and Cochrane Library databases using a variety of keywords. Data were collected on changes in clinical symptoms, inflammatory parameters, and gut microbiota composition. Description of the state of knowledge: The accumulated data suggest that probiotics may improve gut function and reduce inflammation in patients with celiac disease. Bacterial strains such as Lactobacillus and Bifidobacterium show the ability to modulate the immune response and improve the integrity of the intestinal barrier. Research suggests that probiotics may alleviate gastroenterological symptoms such as abdominal pain and bloating and promote the regeneration of intestinal villi. Despite these promising results, there are still no clear guidelines for the use of probiotics in the treatment of celiac disease. Conclusion: In conclusion, probiotic therapy may be a valuable adjunct to a gluten-free diet in patients with celiac disease, offering new therapeutic options and improving quality of life. Further research is needed to establish optimal dosing regimens and to identify the most effective probiotic.